Attractant and growth promoting properties of some feed materials and chemicals incorporated in the diets for Penaeus monodon (Fabricius) - Ali, S Ahamad; Gopal, C; Ramana, J V (Indian Journal of Fisheries, 2011)
Three feed materials, fish meat (from oil sardines) paste, squid mantle paste and clam meat (Meritrix sp.) paste, and three chemical compounds, trimethyl amine, trimethyl amine oxide, and dimethyl sulphone were evaluated for theirattractant and growth promoting properties for Penaeus monodon. The materials were individually incorporated in a semi-purified diet consisting of casein (40%) and gelatin (10%), fish oil (6.0%) and bread flour (33%) along with vitamins, minerals, filler and binder at specific levels ; while the natural materials were included each at 0.5% (on dry matter basis), the other compounds were incorporated at 0.01% level. The shrimp approached the diet containing dimethylsulphone (DMS) in the quickest time of less than 5 minutes on anaverage, followed by the diet with trimethylamine oxide (TMO) in 7.2 minutes. These are followed by trimethyl amine (TMA) to which diet the shrimp approached and picked up in 14.2 minutes. Among the natural materials tested, the diets containing fish meat paste (FMP), clam meat paste (CMP) showed better attractant property. The results showed that the materials tested elicited positive response as feed attractants with varying degree. The results also showed that DMS and TMO seem to possess the highest attractant property to theshrimp. Consumption of diet increased with feed additives, compared to the control diet with TMO and DMS diets recording the highest consumption. The feed additives tested also resulted in growth enhancement of shrimp.